Rapamycin Improves the Response of Effector and Memory CD8+ T Cells Induced by Immunization With ASP2 of Trypanosoma cruzi - Moraschi, Barbara Ferri; Noronha, Isaú Henrique; Ferreira, Camila Pontes; Cariste, Leonardo M.; Monteiro, Caroline B.; Denapoli, Priscila; Vrechi, Talita; Pereira, Gustavo J. S.; Gazzinelli, Ricardo T.; Lannes-Vieira, Joseli; Rodrigues, Maurício M.; Bortoluci, Karina R.; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Deficiency in memory formation and increased immunesenescence are pivotal features of Trypanosoma cruzi infection proposed to play a role in parasite persistence and disease development. The vaccination protocol that consists in a prime with plasmid DNA followed by the boost with a deficient recombinant human adenovirus type 5, both carrying the ASP2 gene of T. cruzi, is a powerful strategy to elicit effector memory CD8+ T-cells against this parasite. In virus infections, the inhibition of mTOR, a kinase involved in several biological processes, improves the response of memory CD8+ T-cells. Therefore, our aim was to assess the role of rapamycin, the pharmacological inhibitor of mTOR, in CD8+ T response against T. cruzi induced by heterologous prime-boost vaccine. For this purpose, C57BL/6 or A/Sn mice were immunized and daily treated with rapamycin for 34 days. CD8+ T-cells response was evaluated by immunophenotyping, intracellular staining, ELISPOT assay and in vivo cytotoxicity. In comparison with vehicle-injection, rapamycin administration during immunization enhanced the frequency of ASP2-specific CD8+ T-cells and the percentage of the polyfunctional population, which degranulates (CD107a+) and secretes both interferon gamma (IFNg and tumor necrosis factor (TNF). The beneficial effects were long-lasting and could be detected 95 days after priming. Moreover, the effects were detected in mice immunized with ten-fold lower doses of plasmid/adenovirus. Additionally, the highly susceptible to T. cruzi infection A/Sn mice, when immunized with low vaccine doses, treated with rapamycin, and challenged with trypomastigote forms of the Y strain showed a survival rate of 100%, compared with 42% in vehicle-injected group. Trying to shed light on the biological mechanisms involved in these beneficial effects on CD8+ T-cells by mTOR inhibition after immunization, we showed that in vivo proliferation was higher and cell viability was not affected by rapamycin treatment. Taken together, our data provides a new approach to vaccine development against intracellular parasites, placing the mTOR inhibitor rapamycin as an adjuvant to improve effective CD8+ T-cell response.